Penegakan Peraturan Gubernur Bali Nomor 10 Tahun 2021 dalam Tatanan Kehidupan Era Baru - I Putu Aris Sedana Putra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
The emergence of the Covid-19 pandemic has claimed many lives and has an impact on all aspects of the state, the Indonesian Government issued Presidential Decree No. 11 of 2020 concerning Public Health Emergencies as a serious warning of health threats. Dishonesty in conveying information on patients suspected of being infected with COVID-19 is categorized as hindering the prevention of outbreaks that can threaten the lives of people around them, including the health workers who handle them. The act of obstructing the handling of the epidemic can be punished. The purposes of this study are to analyze the legal regulation of health protocols in the new life order and the sanctions for people who do not heed the Governor's Regulation No. 10 Year 2021 in Bali. This research method uses a normative legal research type with a statutory concept approach. Data collection techniques were carried out by examining existing library materials. The legal sources used are divided into two, namely primary and secondary legal sources which are then processed and analyzed systematically. The conclusion from the results of the research that has been carried out is that the application of strict sanctions to actions that hinder the prevention of epidemics is punishable by law number 4 of 1984 concerning Communicable Disease Outbreaks article 14 paragraphs (1) and (2). The government seeks to protect health workers as the vanguard of handling the threat of COVID-19 in a preventive and repressive manner. For this reason, it is necessary to disclose one's own health information by disclosing his health condition honestly to health workers to get the right treatment.